The taxonomic status of the Damaraland Redbilled Hornbill (Tockus erythrorhynchus damarensis) : a behavioural, morphological and molecular analysis - Ferguson, J. Willem H. (University of Pretoria, 2013)
Dissertation (MSc (Zoology))--University of Pretoria, 2007.